Zakat, infaq, sadaqa, waqf, and qardhul Hassan in alleviating poverty for micro enterprises: a case of Baitul Maal wat tamwil in Indonesia - Abdul Razak, Dzuljastri; Dawami, Qosdan; Mohamed Zakaria, Fodol (2019)
The challenge of mitigating poverty remains one of the greatest issues affecting humankind. The number of people living in extreme poverty globally amounted to 736 million (UNDP, 2019). In Indonesia, the population living in poverty are in huge numbers amounting to, 25.95 million people (BPS, 2018). Despite of several schemes implemented by the government, the issues of poverty remains inevitable. The purpose of the study is to examine the structure of Baitul Maal Wat Tamwil institution (BMT) which has been playing a pivotal role in poverty alleviation since 1995 albeit facing some issues in its operations. It utilizes the concepts of Zakat, Infaq, Sadaqa and Waqf and Qardhul Hasan (ZISWAQ) which are based on Shariah principles. This study employed content analysis to evaluate the issues and effectiveness of BMT from previous studies and secondary sources. The results indicated that these concepts can indeed be used. However, there are operations issues and that BMT has to address so that it can improve its effectiveness and successfully carry out its role in uplifting the social welfare of microenterprises and the poor.